Deposition of sediments in detention pond - Ismail, Tarmizi (Faculty of Civil Engineering, 2010)

(untitled)
Suspended sediment is the pollutant of primary concern to the urban rivers that results in adverse environmental and economical effect. Detention pond may become the structure that can be indirectly used to remove a portion of suspended sediment. Although the ponds were initially designed to control the increased quantity of runoff associated with impervious areas in the urban landscape, the ponds have been increasingly used to reduce the concentration of contaminants in the runoff. Experiments on deposition of sediments in detention pond and other related aspects such as sediment concentration dispersion and efficiency of the pond were investigated in this study. The kaolin concentration (150 mg/L) has been used as a cohesive sediment material and the range of the discharge is from 0.006 m3/s to 0.016 m3/s. For horizontal distribution, as the diameter of sediment particle is 0.013 mm and particle settling velocity, ?s = 0.8 x 10-4 m/s, the shear flows and settling velocities give an effect of sediment concentration in the detention pond. As the time increases, the sediment concentration decays. The vertical distribution of suspended sediment concentration is uniform according to the small Rouse number at each point. The deposition rates depend on inlet velocity of the pond, an increase from 4.725 x 10-3 g/sec m2 in inlet area to 5.715 x 10-3 g/sec m2 at outlet area. The sediment trap efficiencies of the model is 20 % which is less than the sediment trap efficiency of the prototype due to only cohesive sediment material was used in this experiment